Silicon uptake and isotope fractionation dynamics by crop species - Frick, Daniel A.; Remus, Rainer; Sommer, Michael; Augustin, Jürgen; Kaczorek, Danuta; von Blanckenburg, Friedhelm (Biogeosciences, 2020)
That silicon is an important element in global biogeochemical cycles is widely recognised. Recently, its relevance for global crop production has gained increasing attention in light of possible deficits in plant-available Si in soil. Silicon is beneficial for plant growth and is taken up in considerable amounts by crops like rice or wheat. However, plants differ in the way they take up silicic acid from soil solution, with some species rejecting silicic acid while others actively incorporate it. Yet because the processes governing Si uptake and regulation are not fully understood, these classifications are subject to intense debate. To gain a new perspective on the processes involved, we investigated the dependence of silicon stable isotope fractionation on silicon uptake strategy, transpiration, water use, and Si transfer efficiency. Crop plants with rejective (tomato, Solanum lycopersicum, and mustard, Sinapis alba) and active (spring wheat, Triticum aestivum) Si uptake were hydroponically grown for 6 weeks. Using inductively coupled plasma mass spectrometry, the silicon concentration and isotopic composition of the nutrient solution, the roots, and the shoots were determined. We found that measured Si uptake does not correlate with the amount of transpired water and is thus distinct from Si incorporation expected for unspecific passive uptake. We interpret this lack of correlation to indicate a highly selective Si uptake mechanism. All three species preferentially incorporated light 28Si, with a fractionation factor 1000×ln (α) of −0.33 ‰ (tomato), −0.55 ‰ (mustard), and −0.43 ‰ (wheat) between growth medium and bulk plant. Thus, even though the rates of active and passive Si root uptake differ, the physico-chemical processes governing Si uptake and stable isotope fractionation do not. We suggest that isotope fractionation during root uptake is governed by a diffusion process. In contrast, the transport of silicic acid from the roots to the shoots depends on the amount of silicon previously precipitated in the roots and the presence of active transporters in the root endodermis, facilitating Si transport into the shoots. Plants with significant biogenic silica precipitation in roots (mustard and wheat) preferentially transport silicon depleted in 28Si into their shoots. If biogenic silica is not precipitated in the roots, Si transport is dominated by a diffusion process, and hence light silicon 28Si is preferentially transported into the tomato shoots. This stable Si isotope fingerprinting of the processes that transfer biogenic silica between the roots and shoots has the potential to track Si availability and recycling in soils and to provide a monitor for efficient use of plant-available Si in agricultural production.